The Impact of Job Demands and Resources on Overtime Work and Work-Related Health among Employees of The Isfahan Metro Company - Zohre Sharei; Shahin Ebrahimi (بهداشت و ایمنی کار)
Introduction: The increasing advancement of technology in the field of digital technology and automation has led to a change in the line of work and job content, and it seems that organizations are pushing their employees towards harder and longer work, which affects the health of employees. This study investigated the impact of job demands and resources on overtime and work-related health through the mediation of workaholism and work engagement. Material and Methods: The work is a descriptive survey in terms of purpose and nature. The study’s statistical population consisted of employees of Isfahan Metro Company (320 people), of which (175 people) were studied by Simple Random Sampling. To collect the required information, Spence and Robbin’s (1992) Addiction Questionnaire, Lodahl and Kejner’s (1965), Langseth-Eide’s (2019) Perceived Health-Related Questionnaire, and Bryson Bangers’ Caricature Content (1998) were distributed and supplemented based on a Likert scale. A Structural equation model (SEM) was used to test the hypotheses. Results: The results showed that job demands on workaholism (β=0.394, T=5.969, P <0.05) and job resources had a positive and significant relationship with work engagement (β =0.502, T =7.832, p <0.05), and workaholism and work engagement on the relationship between job demands and resources over time and health. Mediating work-related perceptions (Z= 4.383, Z= 2.189, Z= 3.797). In addition, job resources did not moderate the relationship between job demands and workaholism (β= -0.049, T =1.333, p> 0.05). Conclusion: The results of this study showed that there is a distinction between workaholism and work engagement as two different types of hard work (i.e., negative and positive) in the health process in the JD-R model.